The design of OpticalGamification (OG) with random model in learning interference and diffraction - Saprudin Saprudin; Liliasari Liliasari; Ary Setijadi Prihatmanto; Andhy Setiawan; Fatma Hamid (Momentum: Physics Education Journal, 2021)
This article describes the design and preliminary field testing of using a gamification-application with random model in the learning process of interference and diffraction topics for pre-service physics teachers (PPT). The gamification-application in this research is called OpticalGamification (OG) featuring random model. This research is a quasi-experimental research with a time-series design involving 34 PPT at a university in the city of Jakarta, Indonesia. Data related to the PPT’ concept mastery are collected through test instruments in the form of 50 questions which are an integration of multiple-choice questions, reasoned multiple-choice questions, and essays. This research resulted in a product called OG with random model with several features, including profiles, gamification, forums, achievement pages, projects and leaderboard. The result of preliminary field testing of using the OG with random model shows that the PPT’ concept mastery has increased from series 1 to the next following series.